Peran Guru Pendidikan Agama Kristen sebagai Konselor bagi Perubahan Perilaku Peserta Didik Pendahuluan - Lipus Lipus; Felipus Nubatonis; Esau Yesyurun Tang; Marthen Mau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Christian religious education teachers need to play a role as counselors for behavioral changes in students in elementary education institutions including at the 04 Tahu Public Elementary School, Meranti District. Christian religious education teachers who carry out their main duties at the 04 Tahu Public Elementary School because some students at the school have bad behavior, which includes fighting with their friends, hitting their friends without reason, being lazy to do homework, and there are other problems that they do. This paper aims to explain the role of Christian religious education teachers as counselors in counseling students who have problems or are not problems, so that they experience increasingly significant behavioral changes. The methodology used in this study is qualitative with a data processing approach, namely observation, interviews and documentation. The formulation of the theoretical results of this thesis is that if Christian religious education teachers play a better role optimally, then students will experience behavioral changes that are expected by many people. Thus, the simple conclusion of this thesis is that the role of Christian religious education teachers is highly expected to play a major role in making behavioral changes for students, especially students at the 04 Tahu Public Elementary School.